PENINGKATAN EFEKTIVITAS BELAJAR TOLAK PELURU MELALUI PENGGUNAAN MEDIA PELURU TIRUAN DARI BOLA PLASTIK PADA SISWA KELAS VI SEMESTER 1 SDN BABADAN DEMAK - Mardiwon Mardiwon (Universitas Muria Kudus, 2017)
This research is motivated less availability of instructional media shot put. So it needs to be replaced with another form of media-made bullets. The study design used is classroom action research. After carrying out repairs learning, student achievement is increasing both the first cycle and the second cycle. The results showed that (a) the activity of pre-cycle students by 50%, the first cycle of 70%, then the second cycle by 80% this means that there is an increase of 20% and 10%; (B) the activities of teachers by 75% pre-cycle, the first cycle is 95%, then the second cycle of 100% means there is an increase of 20% and 5%; (C) The results of student learning prasiklus son reaches 59%, the first cycle is 95%, then the second cycle of 100%; whereas female student learning outcomes pre-cycle reaches 41%, the first cycle of 79%, then the second cycle of 79%; and whereas (d) Response (Level of Satisfaction Study) students, achieve student response rate of 85%, has the following criteria Very Satisfied. This criterion illustrates that students really happy and really enjoyed the process of learning.